G559 Acceptability of a home-use oral glucose tolerance test kit for screening cystic fibrosis-related diabetes. (May 2019) - Kumarasamy, M; Peters, C; Drew, S; Gordon, H; Dawson, C; Suri, R; Winyard, P; Bedford, H
Abstract : Aim: To establish if the home-use oral glucose tolerance test (OGTT) kit is acceptable as an alternative to the conventional in-hospital test and if this test increases the annual screening rate for cystic fibrosis-related diabetes (CFRD) in children with cystic fibrosis (CF). Research design and methods: This was a prospective, single centre, cohort study. Children with CF were provided with an OGTT kit to perform the test at home and return the detachable data recorder for analysis and interpretation. Children with CFRD were excluded from the study. Thirty-four children consented to participate and 29 children completed the study. Feedback questionnaires were provided with the OGTT kits and 16 of these were returned. Results: Twenty-seven OGTT procedures were successfully completed at home on the first attempt. All parents (100%) and 14 children (88%) reported that the kit was easy to use. Thirteen parents (81%) and 11 (69%) children preferred the home-use OGTT to the in-hospital OGTT. All parents (100%) of the 11 children who had previously undertaken an in-hospital OGTT preferred home-use OGTT. The uptake of the home-use OGTT for Oct 2015–16 was 74% (n=29). The overall uptake including the conventional in-hospital OGTT (n=3) was 82%. The screening rate was higher compared to the previous two years (Oct 2013–14 and Oct 2014–15); 51% (p=0.002) and 52% (p=0.004) respectively (table 1 ). Conclusion: The home-use OGTT kit is easy to use, acceptable to patients and preferred to the in-hospital alternative. The convenience and accessibility of home-use OGTT could have a significant impact on the screening rate for CFRD.